Impact of multidisciplinary simulation-based training on patient safety in a paediatric emergency department. Issue 5 (20th December 2012) - Patterson, Mary D; Geis, Gary L; LeMaster, Thomas; Wears, Robert L
Abstract : Background: Cincinnati Children's Hospital is one of the busiest paediatric emergency departments (ED) in the USA; high volume, high acuity and frequent interruptions contribute to an increased risk for error. Objective: To improve patient safety in a paediatric ED by implementing a multidisciplinary, simulation-based curriculum emphasising teamwork and communication. Methods: Subjects included all healthcare providers in the ED. Multidisciplinary teams participated in simulation-based training focused on teamwork and communication behaviours in critical clinical scenarios. The Safety Attitudes Questionnaire, tests of knowledge and evaluations of critical simulations and actual performance in the ED resuscitation bay were assessed. Methods to sustain improvements included mandatory participation of all new staff in simulation-based training and the introduction of routine in situ simulations. Results: 289 participants attended the initial training. 151 participants attended the re-evaluation at a mean of 10.2 months later. Sustained improvements in knowledge and attitudes were demonstrated. Knowledge tests at baseline, postintervention and re-evaluation had scores of 86%, 96% and 93%, respectively. Friedman's test analysis of SAQ scores at baseline, postintervention and re-evaluation indicated significant attitude changes. The ED with a preintervention baseline of 2–3 patient safety events per year has now sustained more than 1000 days without a patient safety event. This improvement occurred even though the time required in initial simulation training has been condensed from 12 to 4 h. Conclusions: Simulation training is an effective tool to modify safety attitudes and teamwork behaviours in an ED. Sustaining cultural and behavioural changes requires repeated practice opportunities.